PENGARUH PENGENDALIAN INTERNAL, AKUNTABILITAS, TEKANAN EKSTERNAL DAN KOMITMEN PIMPINAN TERHADAP PENERAPAN TRANSPARANSI PELAPORAN KEUANGAN (Studi Empiris Pada SKPD Kota Pekanbaru) - Amelia, Rossa; Agusti, Restu; Natariasari, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this research was to examine the influence of internal control, accountability, external pressure and leader commitment on transparency of financial reporting. This research is expected to help the government in order to improve the transparency of financial reporting increasingly better in the future. The sample used in this research are the echelon IV and accounting department in Pekanbaru City Government. Data was collected through questionnaire survey method. The data was collected by using 96 questionnaires that spread to 32 SKPD (regional work units). Data were analyzed by using multiple regression (multiple regression) and moderate regression (Moderate Regression Analysis-MRA) with the help of a computer program SPSS version 17.0. The results showed that internal control, accountability, external pressure and leader commitment had significant influence on transparency of financial reporting.Keywords: transparency, accountability, pressure, and commitment.